Media and Foreign Policy on Pak-Afghan Relations (1997-2005): The Role of US and Pakistani Press - Iqbal, PhD , Ashraf; Hussain, Tanveer; Javed, Naeem (Journal of Peace, Development and Communication, 2020)
The main purpose of the present research is to investigate Pak-Afghan relations in the editorials of US newspapers, The Washington Post & The New York Times and Pakistani newspapers Dawn & The News related to the following issues during the period 1997-2005; A) US as a factor in Pak-Afghan relation, B) Coverage of Islam/Muslims regarding war on terrorism, C) Pakistan’s stance on Pak-Afghan bilateral relations, and D) US’s stance on Pak-Afghan bilateral relations. The time period to be examined in this proposed study spans over eight years regarding the editorial coverage of Pak-Afghan relations in the US and Pakistani leading English Press. Triangulation method based on qualitative and quantitative method was used to conduct the present research. The results show that the editorial contents of USA and Pakistani newspapers were not different regarding Pak-Afghan relations before and after 9/11. The incident of 9/11 changed the American foreign policy towards developing and least developing nations especially Muslims states like Pakistan, Afghanistan, Iraq, and Iran etc. Pakistani press highlighted the issues regarding the Pak-Afghan relations before and after 9/11 as a favorable and conducive, related to Muslim/Islam regarding war on terrorism. The study suggested that instead of the focus on military resolution of the different problems, rather social bilateral negations should be prioritized which would be long lasting and full of mutual respects and honor.